Evidence-based medicine: An update on treatments for peritoneal dialysis-related peritonitis - Pasqual Barretti (2015)
Peritonitis continues to be a major complication of peritoneal dialysis (PD), and adequate treatment is crucial for a favorable outcome. There is no consensus regarding the optimal therapeutic regimen, and few prospective controlled studies have been published. The objective of this manuscript is to review the results of PD peritonitis treatment reported in narrative reviews, systematic reviews, and proportional meta-analyses. Two narrative reviews, the only existing systematic review and its update published between 1991 and 2014 were included. In addition, we reported the results of a proportional meta-analysis published by our group. Results from systematic reviews of randomized control trials (RCT) and quasi-RCT were not able to identify any optimal antimicrobial treatment, but glycopeptide regimens were more likely to achieve a complete cure than a first generation cephalosporin. Compared to urokinase, simultaneous catheter removal and replacement resulted in better outcomes. Continuous and intermittent IP antibiotic use had similar outcomes. Intraperitoneal antibiotics were superior to intravenous antibiotics in reducing treatment failure. In the proportional meta-analysis of RCTs and the case series, the resolution rate (86%) of ceftazidime plus glycopeptide as initial treatment was significantly higher than first generation cephalosporin plus aminoglycosides (66%) and glycopeptides plus aminoglycosides (75%). Other comparisons of regimens used for either initial treatment or treatment of gram-positive rods or gram-negative rods did not show statistically significant differences. The superiority of a combination of a glycopeptide and a third generation cephalosporin was also reported by a narrative review study published in 1991, which reported an 88% resolution rate.